The study of the carcasses of effect different types of vertebrate carcasses on the numbers and the species of attracting insects in Alsalamia – Alhusseinia region /Karbala province. - AL-Jamali, Nassir Abdulsahib; AL-Mafragi, Zahraa jawad kadem (Journal of Kerbala for Agricultural Sciences, 2018)
The acknowledgement of the biology attracting insect and its ecology of the killing method animals crime place was an important method of in detection, when the crime was happened.so it must be important to know the species of forensically important insects This study aimed to detect the effect of the types of the animal carcass on the numbers and species of attracting insects. The study conduct in Al-Salamia – Al-Husseinia region Karbala province in 2017 it used three types of vertebrate: dogs, rabbits and cats. Daily it recorded field observation of these carcasses of every day animas from the begin of killing of these animal passing through all stages of decomposition which recording of the species and numbers of attracted insects was done. The result shows 13 species be longs to diptera order and four families, six species belong coleoptra order and four families and many species of the order hymenoptera belong to 2 families : The insect species that belong to the Diptera order according to it is four . 1- Calliphoridae family Calliphora viciana, Chrysomaya albiceps,Chrysomaya Megacephala,Chrisomaya putoria,Lucilia sericata, Lucilia cuprina .and Lucilia spp. 2- Sacrophagidae family: Sacrophga africa,Sacrophaga frenata, and Sacrophaga spp. 3- Muscidae family : Musca domestica,Muscina stabulans. 4- Otitidae: Physiphora demandata. The types of insect belonged to order Coleo 1- Histiridae family: Saprinus subnitescens. 2- Dermistedae family : Dermestes maculates, Dermestes sp 3- Cleridae family: Necrobia rufipes. 4- Staphylinidae family : Gauropterus fulgiaus and Anotylus sp. The types belong to order Hymenoptera was: Formicidae family different species. Vespidae family: Vespa orientalis